Rewiring the seizing brain: stem cell grafts as neuromodulatory architects in epilepsy therapy - Wang, Zijie; Ma, Yanan; Hu, Xiqi; Xia, Ying (Frontiers in Neurology, 2025)
As an emerging therapeutic strategy, stem cell transplantation has demonstrated promising potential in the management of refractory epilepsy. Epilepsy, a prevalent neurological disorder characterized by recurrent seizures, affects approximately one-third of patients worldwide who exhibit resistance to existing antiepileptic drugs (AEDs). Consequently, exploring novel treatment modalities is imperative. Recent studies have indicated that stem cell transplantation improves neurological function in epilepsy through multiple mechanisms. Research has revealed that transplanted stem cells mitigate seizure-induced neuronal damage by replacing dead or dysfunctional neurons, secreting beneficial neurotrophic factors (e.g., brain-derived neurotrophic factor, BDNF), and releasing anti-inflammatory cytokines. Preclinical studies and early-phase clinical trials have shown that stem cell transplantation significantly reduces seizure frequency and enhances patients’ quality of life. However, current research is limited by small sample sizes and short-term follow-ups, necessitating further validation of long-term efficacy. Despite its therapeutic promise, stem cell transplantation faces critical challenges. First, technical details such as the cell source, processing, method of transplantation, and timing have yet to be standardized, leading to potential variability in efficacy and safety across different stem cell types. Second, complications like immune rejection and tumorigenesis pose significant safety risks. Future research should focus on optimizing stem cell selection and processing, designing robust clinical trials to evaluate long-term safety and efficacy, exploring combinatorial approaches with existing therapies, and developing advanced biomaterials to enhance transplantation success. Additionally, monitoring post-transplant cell survival and functionality, along with identifying epilepsy-specific biomarkers, will be crucial to refining the precision and safety of stem cell-based therapies.